Effect of different concentrations of metal ions on alpha amylase production by Bacillus amyloliquefaciens - ., Sudha (Research in Biotechnology, 2012)
Bacillus amyloliquefaciens is obtained from soil which produces extracellular alpha amylase enzyme. The present study is concerned with effect of metal ions on alpha amylase production. Metal ions are Ca2+, Cu2+, Mg2+, Fe2+ and Mn2+ at different concentrations 2g/l, 5g/l and 7g/l. Supplementations of salts of certain ions provide good growth of microorganism and production of alpha amylase. Ca2+and Mg2+exhibit positive influence on alpha-amylase production. Our results show that the amylase production is higher in the presence of Ca2+ (0.439) IU/ml/min at 7g/l concentration in comparison of other metal ions. The enzyme activity of Mg2+(0.321) IU/ml/min at 2g/l concentration. The study focuses on supplementation of metal ions increase the production of amylase.